Frequency and Correlation of Fingerprints and Lip Prints with ABO Blood Groups among Nkalaha of South-Eastern Nigeria - Monday N. Chima; Ojims Ewunonu; Darlington-Peter Chibuzor Ugoji; Johnbosco E. Mamah; Paschal Chijioke Okoye; Kelvin E. Ortuanya (Nigerian Journal of Medicine)
Background: Forensic individual identification system is one of the accurate ways of identification. The need to improve existing methods continues to be an area of research. OBJECTIVE: This study aimed to investigate the frequency and correlation of different lip print patterns and fingerprint pattern distribution compared with gender and ABO blood group. Methodology: The study was conducted on 200 healthy volunteers aged 15–50 years. Each subject’s thermoscopic and dermatographic data were analysed according to Suzuki, Tsuchihashi, and Henry classification systems. ABO blood test was done and recorded for each subject. Pearson statistics were done, and tests were considered statistically significant when the P value was at 0.05; a Bar chart was applied to analyse the prevalence of the variables. Results: The O blood group was noted as common among the genders, followed by A, while the least was AB. Type III lip print pattern was the most predominant, while the least common was Type V in both genders. The radial loop fingerprint pattern was the most common in both genders, followed by Whorl, while Arch was least noted in males and tented loop in females. A significant correlation was found between ABO and lip print patterns except for Type V in both genders. A positive correlation was observed between all the ABO with fingerprint patterns, except for A and TL (A with fingerprint: r = 1, P = 0.05, B: r = 0.889, P = 0.001, O: r = 0.976, P = 0.000 and AB: r = 0.120, P = 0.742). Conclusion: We found an association between lip print patterns and fingerprints with ABO in both genders; thus, correlating this physical evidence sometimes helps the forensic team get an accurate personal identification or narrow the search for an individual where no possible data refer to the subject’s identity.